Izseljevanje iz Ribniške doline od srede 19. stoletja do druge svetovne vojne - Ceglar, Dean (Dve domovini, 2001)
Peddlery presents the oldest form of emigration from the river Ribnica valley. Similar to other Slovene provinces this valley was captured by an emigration wave at the end of the 19th century; it was directed mainly to the U.S.A. The year 1945 and the arrival of new authorities also triggered emigration from the valley. Peddlery nowadays still exists.
Keywords: 1850-1941; Ribnica; Ribniška dolina; slovenski izseljenci